Concentração, proporção molar e taxa de produção de ácidos graxos voláteis (AGV) no rúmen de bovinos alimentados com diferentes níveis de concentrado na dieta - Berchielli, Telma Teresinha [UNESP]; Rodriguez, Norberto Mário; De Andrade, Pedro [UNESP] (My University, 1996)
This work was conducted to study the concentration, molar proportions, rates of the VFA production (acetate, propionate, butirate, and the total VFA) and the correlation of concentration (mmoles/ 1) versus production relative rate of VFA (mmoles/min). Three of ruminally-canulajed steers were fed with forage: concentrate ratios of 80:20, 60:40 and 40:60. a single infusion of (Na-acetate-14C in to the rumen was to used measure the relative rate of production of VFA. The concentation of VFA (mmol%) changed for propionate and bretyrate as the concentrate level increased form 20 to 60% the acelate and total VFA concentrations were not affected by the treatments although a decrease in acetate was observed at the higher concentrate level, and a increase in total VFA, as the concentration of propionate increased. The acetate: propionate ratios for the treatments 80:20; 60:40; 40:60 were 5.1; 4.8; and 3.8, respectively, and were statistically different. Relative production rates increased from 35.2 to 48.9; for 7.0 to 13.0; for 4.0 to 6.8; and for 46.2 to 68.7 moles/24 hours for acetate, propionate, butirate and total VFA, respectively, as the concentrate in the diet increased. It was observed that the concentration and the rate production of propionate and butyrate were highly correlated (0.83 and 0.91, respectively). However, for acetate were low correlation (0.05), and average correlation (0.51) for total UFA's.
Concentration, molar proportions, and production of volatile fatty acids (VFA) in the rumen cattle fed different levels of concentrate in the diet
Keywords: Concentration; Molar proportions; Production rate; Volatil fatty acid